Stochastic modelling and optimisation of multi-plant capacity planning problem. (9th December 2014) - Verma, Anoop; Shukla, Nagesh; Tyagi, Satish; Mishra, Nishikant
In this paper, the problem of capacity planning under risk from demand and price/cost uncertainty of the finished products is addressed. The deterministic model is extended into a two-stage stochastic model with fixed recourse by means of various expected levels of demand as random. A recourse penalty is also included in the objective for both shortage and surplus in the finished products. The model is analysed to quantify the risk using Markowitz mean-variance model.